Esophageal tuberculosis with Esophagopulmonary fistula: A case report (Indian Journal of Case Reports, 2021)
Esophageal tuberculosis (TB) is a rare manifestation of tuberculosis with secondary involvement being more common. The most common presentation is with dysphagia and a high index of suspicion for a tubercular etiology should be kept in mind, especially in a TB endemic region like India. Early diagnosis is essential to prevent complications such as bleeding, perforation, or stricture and also because the disease is curable with antitubercular therapy. We present a case report of a young female who presented to our hospital with complaints of cough and dysphagia and was subsequently diagnosed with esophageal tuberculosis complicated by an esophagopulmonary fistula.